A novel missense mutation in the FGB gene (p.Gly302Arg) leading to afibrinogenemia - Ivaškevičius, V.; Rühl, H.; Detarsio, G.; Biswas, A.; Gupta, S.; Davoli, M.; Quartara, A.; Pérez, S.; Raviola, M.; Oldenburg, J. (Hämostaseologie, 2016)
Afibrinogenemia represents the rarest form of fibrinogen deficiency. Causative missense mutations occur rarely and may improve the understanding of fibrinogen structure and function. Patients and methods: The propositus was a 26-year-old Argentinian with afibrinogenemia. FGA, FGB and FGG exons and flanking regions were screened by sequencing and the mutant protein was analyzed in silico. Results: A novel missense mutation in the FGB gene (Bbeta Gly272Arg, p.Gly302Arg) was identified. In silico analysis revealed its location in a highly conserved region, which preserves the core fold of the C-terminal beta-chain and is important for proper secretion. A substitution by a positively charged large Arg residue in this area would most likely disturb the core fold by additional interactions with adjacent residues (p.Asp291, p.Asp297, p.Asp311), or by forming of non-native interactions with other proteins, thereby hindering the action of molecular chaperones. Both alternatives would disturb the regular secretion of the beta-chain. Conclusions: The novel mis-sense mutation in the FGB gene causes afibrinogenemia most probably by affecting the secretion of the fibrinogen beta-chain.
Keywords: Fibrinogen; Afibrinogenemia; bleeding; FGA; FGB; FGG